Nanoprobes for Tumor Theranostics - Shen, Zheyu (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book reports cutting-edge technology in nanoprobes or nanobiomaterials used for the accurate diagnosis and therapy of tumors, involving a multidisciplinary of chemistry, materials science, oncology, biology, and medicine.